HUBUNGAN ANTARA PERUBAHAN TUTUPAN LAHAN TERHADAP TOTAL PENDUDUK YANG DIPENGARUHI OLEH FENOMENA URBANISASI DI BOGOR, JAWA BARAT - Sukma Sakti Agita Hermanto; Afra Donatha Nimia Makalew; Bambang Sulistyantara (Jurnal Lanskap Indonesia, 2018)
Urbanization is the main issue that altered the environmental condition nowadays. Urbanization means that there are changes in suburban areas to fulfill the function needed in the urban area. Nowadays, urbanization occurred due to the high demand of housing area with lower budget and comfortable environment of living condition. This condition was presented in the Bogor city case. Bogor is one of the oldest cities in Indonesia which is located in the southern part of Jakarta. Due to the increase of population in the capital city and increased of the higher price of housing, people started to looked for place to stay outside the city. Bogor located in the strategic location just close enough for people to commute to Jakarta. The transit city transform into commuting city. People works in Jakarta wanted to live in a more comfortable place of living and cheaper in price than the capital city started to see Bogor as an opportunity. Based on the data obtained by the Central Bureau of Statistics Jakarta in 2015, there are 187.777 total people commuted daily from Bogor to Jakarta. This condition also triggered by the better quality of access in and out Bogor. Mass rapid transportation and highway toll gate create more land cover changes potential to fulfill the high demand of housing. Thus, this research aimed to see the effect of highway toll gate in the land use cover change in Bogor city. Landsat Images was used using the time-series method started since 1978 (the official year of Jagorawi Toll gate operation) with the 10 years interval time, 1989, 1999, 2009 and 2016. In determining the land use cover change, NDVI method was used which has been widely applied in detecting the greeneries. The result then evaluated using the supervised classification and validated using the Kappa Accuracy test. The result of this research shows that land use cover change corresponded with the total population in the citizenship census 2009. Total built area in 2009 is 36.20% which increased by 8.46% since 1999, this result suitable with the total population 949.000 in 2009 Citizenship census which increased by 364.000 since 1999. The highest built area detected is 42.15% in 2016 with total of 1.030.720 population and three active Highway toll gate operated.